The Effect of Organizational Citizenship Behavior on the Work Productivity of Employees at the Padang City Investment and One-Stop Integrated Services Agency - Rahmi Wahyuni; Syamsir Syamsir (Darul Yasin Al Sys, 2026)
Employee productivity in public service agencies is a key determinant of service quality received by the public. At the Padang City Investment and One-Stop Integrated Service Agency (DPMPTSP), low productivity is reflected in 22 disciplinary violation cases in 2023, a low staff competence and attitude score in the Public Satisfaction Index (78.5), and a 63.8% increase in public complaints from 2022 to 2023. This condition is considered closely related to the suboptimal implementation of Organizational Citizenship Behavior (OCB) among employees. This study aims to examine the effect of OCB on employee work productivity at the DPMPTSP of Padang City. A quantitative correlational approach was employed using total sampling, involving all 50 employees as respondents. Data were collected through a Likert-scale questionnaire measuring OCB based on the five dimensions proposed by Organ et al. (2006), namely altruism, conscientiousness, sportsmanship, courtesy, and civic virtue, as well as work productivity based on the six indicators proposed by Sutrisno (2011). Data were analyzed using classical assumption tests and simple linear regression with SPSS. The findings indicate that OCB has a positive and significant effect on employee work productivity, as shown by a t-test significance value of 0.000 (< α = 0.05) and a positive regression coefficient of 0.617. The regression equation is Ŷ = 27.581 + 0.617X. The Pearson correlation coefficient of r = 0.545 indicates a moderately strong positive relationship, while the coefficient of determination (R²) of 0.297 shows that OCB explains 29.7% of the variability in work productivity. This study concludes that strengthening OCB culture, particularly in the dimensions of conscientiousness, altruism, and civic virtue, is a relevant and measurable strategy for improving employee productivity in public service agencies. Theoretically, this study contributes to the literature on organizational behavior and public human resource management, while practically, it provides implications for strengthening employee behavior-based productivity strategies in local public service institutions.